Management of Village Owned Enterprises (BUMDES) in Increasing Village Economic Income in Banyumas Regency, Indonesia - Laksana, Rio Dhani; Adi, Pramono Hari; Nurfitri, Titi (AIBPM Publisher, 2023)
In general, signs of BUMDes' success include steadily rising revenues and assets, a widening customer base, staff members who are able to do their jobs, and a positive influence on local communities. BUMDes that are constructed sporadically assist the community. This is brought on by persistent management system shortcomings, unsolved capital-related barriers, and the requirement to boost the caliber of human resources. This study employs a descriptive qualitative methodology and the Donald van Metter and Carl van Horn theory of A Model of Policy Implementation. In the Indonesian province of Banyumas, the study included a sample of 80 BUMDES. Observation, interviews, and documentation studies were the data gathering methods employed. Purposive sampling was performed as part of the informant selection process. The findings suggested that the BUMDes initiative may have been implemented more effectively. The village side anticipates an increase in local income as a result of the development of BUMDes. However, adopting it faces several challenges, including a lack of socialization of BUMDes work, widespread coverage, the managers' poor managerial skills, and little understanding of BUMDes management.